What is Pleasure? The Relation Between the Two Definitions of Pleasure Given by Aristotle in his Nicomachean Ethics - Lawrence, L.C., Adrian Alexander (Alpha Omega, 2021)
Summary: This article discusses the nature of “pleasure” in Aristotle. It is an attempt to reconcile and integrate the two different definitions that Aristotle gives in 1153a12–15 (unimpeded activity) and 1174b31–33 (end that completes an activity) of his Nichomachean Ethics. It exams the analysis and proposals of three contemporary philosophers: G.E.L. Owen, David Bostock, and Michael Pakaluk. It then passes to the exegesis of the medieval Thomas Aquinas. Thomas’s reading of the texts is presented as a way to answer the difficulties brought up earlier and provide a solid interpretation that is capable of uniting both of the definitions of the Stagirite. Key Words: Pleasure, unimpeded activity, end, complete, Aristotle, G.E.L. Owen, David Bostock, Michael Pakaluk, Thomas Aquinas. Sommario: Questo articolo discute la natura del “piacere” in Aristotele. È un tentativo di riconciliare e integrare le due diverse definizioni che Aristotele dà in 1153a12-15 (attività non-impedita) e 1174b31-33 (fine che completa un’attività) della sua Etica Nicomachea. Esamina l’analisi e le proposte di tre filosofi contemporanei: G.E.L. Owen, David Bostock e Michael Pakaluk. Si passa poi all’esegesi del medioevale Tommaso d’Aquino. La lettura dei testi da parte di Tommaso è presentata come un modo per rispondere alle difficoltà sollevate in precedenza e fornire una solida interpretazione che è in grado di unire entrambe le definizioni dello Stagirita. Parole chiave: Piacere, attività non-impedita, fine, completa, Aristotele, G.E.L. Owen, David Bostock, Michael Pakaluk, Tommaso d’Aquino. Summary a brief statement that presents the main points in a concise form More (Definitions, Synonyms, Translation)